The Prospects of Islamic Economics in the Era of Prabowo-Gibran Leadership - Anisatul Maghfiroh; Imam Muslih; Azwar Cholili; Muh. Syaukin Muttaqin; Ali Arifin (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This study aims to analyze in depth the prospects of the Islamic economy in Indonesia during the Prabowo-Gibran leadership era, identify the opportunities and challenges faced, and formulate strategy recommendations to encourage comprehensive and sustainable Islamic economic growth. Using a qualitative approach through literature study, this study collects and analyzes various related literature sources, such as books, journals, research reports, and other relevant written sources. This research also examines Prabowo-Gibran's vision, mission, and work program related to the development of the Islamic economy in Indonesia. The results showed that the Prabowo-Gibran leadership era had great opportunities in the development of the Islamic banking and finance industry, the Islamic economic sector in the fields of trade, halal tourism, and MSMEs, as well as increasing public literacy and education about the Islamic economy. Supportive regulations and policies, financing, and Islamic economic diplomacy in the global arena are also important prospects in this era. However, the main challenges faced include the availability of competent human resources, competition with conventional economic systems, and harmonization of policies between the center and the regions. This research provides recommendations for strategies that can be applied by the Prabowo-Gibran administration to optimize opportunities and overcome challenges in the development of the Islamic economy in Indonesia